Embroidering Socio-Religious Peace: The Synergy of Muslim and Catholic Youth on the Island of Java Indonesia - Irhas Sabililhaq (Universitas Negeri Jakarta, 2024)
During rampant issues of radicalism and religious fanaticism reported in various newspapers and social media, the presence of young people is needed to become agents of moderation and tolerance. This study aims to understand the role of Muslim and Catholic youth in creating a moderate and tolerant society. This research uses a descriptive qualitative approach. Research location: Kenteng Hamlet, Kembang Village, Kapanewon Nanggulan, Kulon Progo Regency, Yogyakarta Special Region Province. Data collection techniques were conducted by interview, observation, and documentation. This research resulted in the following findings, namely: 1) The values of moderation and tolerance applied in the community can be indicated through several things, namely the willingness to accept differences, prioritize communication and dialogue, and others. 2) The role of Muslim and Catholic youth in creating a moderate and tolerant society is done through several approaches, namely: religious approach; sports approach; and social approach.